2022
DOI: 10.1002/prot.26337
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing structural features of proteins from deep‐sea organisms

Abstract: Protein adaptations to extreme environmental conditions are drivers in biotechnological process optimization and essential to unravel the molecular limits of life. Most proteins with such desirable adaptations are found in extremophilic organisms inhabiting extreme environments. The deep sea is such an environment and a promising resource that poses multiple extremes on its inhabitants. Conditions like high hydrostatic pressure and high or low temperature are prevalent and many deep-sea organisms tolerate mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Morris et al found significant increases in the transcription of genes coding GAPDH and the heat shock protein HSP70 in response to high pressure [ 110 ]. Sieg et al compiled a database comparing protein sequences from deep-sea organisms with their orthologous proteins [ 111 ]. As mentioned previously, the stability and flexibility of the deep-sea proteins should change on the way to allow them to be able to function under pressure.…”
Section: Pressure Effect On Some Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Morris et al found significant increases in the transcription of genes coding GAPDH and the heat shock protein HSP70 in response to high pressure [ 110 ]. Sieg et al compiled a database comparing protein sequences from deep-sea organisms with their orthologous proteins [ 111 ]. As mentioned previously, the stability and flexibility of the deep-sea proteins should change on the way to allow them to be able to function under pressure.…”
Section: Pressure Effect On Some Biomoleculesmentioning
confidence: 99%
“…As mentioned previously, the stability and flexibility of the deep-sea proteins should change on the way to allow them to be able to function under pressure. A clear pattern or mechanism for high pressure adaptations was, however, not apparent from the database [ 111 ]. Actin is one of the most basic proteins in all living organisms.…”
Section: Pressure Effect On Some Biomoleculesmentioning
confidence: 99%